Contract law - McKendrick, Ewan (Palgrave Macmillan law masters, 2007)
McKendrick explores the underlying themes and explains the basic rules of English contract law, introducing the current debates about the nature, scope and functions of this law and discussing some of the wider controversies surrounding basic doctrines.